Student Academic Procrastination? Self Esteem, Motivation for Achievement, and Learning Style - Trisnani, Rischa Pramudia; Asri, Dahlia Novarianing (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2024)
Academic procrastination is a tendency to avoid or postpone academic tasks that students often carry out. Many factors cause academic procrastination, including internal and external factors. This study aims to determine the correlation between self-esteem, achievement motivation, and learning style on students' academic procrastination. This study uses quantitative research with a correlational study design. The population of this study is active students of PGRI Madiun University. The sampling technique used was proportional random sampling, and a sample of 586 students was obtained. The data collection technique uses a psychological scale with a Likert Scale model with alternative answers: Strongly Agree, Agree, Disagree, and Strongly Disagree. The self-esteem scale consists of 23 items, the achievement motivation scale consists of 12 items, the learning style scale consists of 30 items and the academic procrastination scale consists of 31 items. The data analysis technique uses product-moment correlation with the help of SPSS 29. The study results showed a significant correlation between self-esteem, achievement motivation, and learning style with academic procrastination.